OPTIMALISASI PENGAWASAN DPS (DEWAN PENGAWAS SYARIAH) DALAM AUDIT LEMBAGA KEUANGAN SYARIAH - Devi Septyani, Sri; Aprianto, Anto (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
ABSTRACT Sharia financial institutions (LKS) have emerged as an important force in building a sustainable and inclusive economy, by integrating sharia principles in financial services. This research aims to explore the role of LKS in empowering the community's economy, especially through financing for micro and small enterprises (MSMEs), as well as the challenges faced in implementing sharia principles. The research method used is qualitative with a literature study approach, which collects data from various literature and related research. The research results show that LKS contributes significantly to increasing financial access, encouraging financial inclusion, and strengthening the MSME sector. However, challenges such as the independence of the Sharia Supervisory Board (DPS), limited human resources, and the public's lack of understanding of sharia financial products still need to be overcome. This research also highlights the importance of collaboration between the government, regulators and financial institutions to strengthen the regulatory framework and increase the competence of DPS. Overall, LKS has great potential in supporting sustainable and inclusive economic development in Indonesia. With a commitment to sharia principles and social responsibility, LKS can act as a key driver in achieving sustainable economic development goals, as well as providing wider benefits to society. Keywords: Sharia financial institutions, Sharia Supervisory Board, sharia audit, sharia compliance